Apolipoprotein L1 Variants and Blood Pressure Traits in African Americans - Nadkarni, Girish N. (J Am Coll Cardiol, 2017)
BACKGROUND: African Americans (AA) are disproportionately affected by hypertension-related health disparities. Apolipoprotein L1 (APOL1) risk variants are associated with kidney disease in hypertensive AAs. OBJECTIVES: This study assessed the APOL1 risk alleles’ association with blood pressure traits in AAs. METHODS: The discovery cohort included 5,204 AA participants from Mount Sinai’s BioMe biobank. Replication cohorts included additional BioMe (n = 1,623), Vanderbilt BioVU (n = 1,809), and Northwestern NUgene (n = 567) AA biobank participants. Single nucleotide polymorphisms determining APOL1 G1 and G2 risk alleles were genotyped in BioMe and imputed in BioVU/NUgene participants. APOL1 risk alleles’ association with blood pressure–related traits was tested in the discovery cohort, a meta-analysis of replication cohorts, and a combined meta-analysis under recessive and additive models after adjusting for age, sex, body mass index, and estimated glomerular filtration rate. RESULTS: There were 14% to 16% of APOL1 variant allele homozygotes (2 copies of G1/G2) across cohorts. APOL1 risk alleles were associated under an additive model with systolic blood pressure (SBP) and age at diagnosis of hypertension, which was 2 to 5 years younger in the APOL1 variant allele homozygotes (Cox proportional hazards analysis, p value for combined meta-analysis [p(com)] = 1.9 × 10(−5)). APOL1 risk alleles were associated with overall SBP (p(com) = 7.0 × 10(−8)) and diastolic blood pressure (p(com) = 2.8 × 10(−4)). After adjustment for all covariates, those in the 20- to 29-year age range showed an increase in SBP of 0.94 ± 0.44 mm Hg (p(com) = 0.01) per risk variant copy. APOL1-associated estimated glomerular filtration rate decline was observed starting a decade later in life in the 30- to 39-year age range. CONCLUSIONS: APOL1 risk alleles are associated with higher SBP and earlier hypertension diagnoses in young AAs; this relationship appears to follow an additive model.